Pengembangan Media Pembelajaran Bahasa Indonesia dalam Bentuk Komik pada Materi Menelaah Struktur dan Kebahasaan Fabel - Aslina Telaumbanua; Noveri Amal Jaya Harefa (Universitas Nias, 2023)
The problem with the learning process at SMP Negeri 1 Sitolu Ori is the lack of variety of learning media used so that many students are unable to learn independently without the presence of a teacher. This study aims to develop appropriate, practical and effective Indonesian language comic media. This type of research is development research using a 4-D model consisting of define, design, develop, disseminate. The instruments used to determine the feasibility of comic media were validation questionnaires for material, language, and design experts, as well as student responses and effectiveness questionnaires. The results of this study are in the form of comic media on the material of examining the structure and language of fables. The assessment of material experts reached 91.25%, linguists reached 92.84%, design experts reached 92.18% with very practical criteria. The results of the assessment on the response questionnaire of individual trial students were carried out in class VII SMP Negeri 1 Sitolu Ori with a total of 3 people obtaining 88.09% in the very practical category. Then it was continued with a small group trial of 5 people obtaining 91.42% in the very practical category. After the small group trials continued with field trials, which were attended by 20 students, the results of the questionnaire obtained a score of 91.07% in the very practical category. Assessment of student learning outcomes tests obtained a percentage of classical completeness in individual trials achieving an effectiveness score of 88%, small group trials achieving a score of 82% with effective criteria, and field trials achieving an effectiveness score of 80.75% with effective criteria. It can be concluded that: comic media is feasible, practical, and effective to use so that it meets the expectations or objectives of the researcher.